2018
DOI: 10.1002/jobm.201800324
|View full text |Cite
|
Sign up to set email alerts
|

Quorum sensing communication: Bradyrhizobium‐Azospirillum interaction via N‐acyl‐homoserine lactones in the promotion of soybean symbiosis

Abstract: Quorum‐sensing (QS) mechanisms are important in intra‐ and inter‐specific communication among bacteria. We investigated QS mechanisms in Bradyrhizobium japonicum strain CPAC 15 and Azospirillum brasilense strains Ab‐V5 and Ab‐V6, used in commercial co‐inoculants for the soybean crop in Brazil. A transconjugant of CPAC 15‐QS with partial inactivation of N‐acyl‐homoserine lactones (AHLs) was obtained and several parameters were evaluated; in vitro, CPAC 15 and the transconjugant differed in growth, but not in bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
3
0
2
Order By: Relevance
“…Besides, Pseudomonas fluorescens has been found to enhance the nitrogen fixation of soybean through promoting the growth and colonization of Bradyrhizobium japonicum [45]. Soybean symbiotic performance was improved by co-inoculation with Bradyrhizobium japonicum and Azospirillum brasilense through quorum-sensing communi-cation [46]. In this study, all the Pseudomonas isolates showed potential to produce IAA, which might influence the symbiotic outcome by altering phytohormonal homeostasis of soybean [47].…”
Section: Discussionmentioning
confidence: 74%
“…Besides, Pseudomonas fluorescens has been found to enhance the nitrogen fixation of soybean through promoting the growth and colonization of Bradyrhizobium japonicum [45]. Soybean symbiotic performance was improved by co-inoculation with Bradyrhizobium japonicum and Azospirillum brasilense through quorum-sensing communi-cation [46]. In this study, all the Pseudomonas isolates showed potential to produce IAA, which might influence the symbiotic outcome by altering phytohormonal homeostasis of soybean [47].…”
Section: Discussionmentioning
confidence: 74%
“…Uno de los mecanismos por los que se produce esta comunicación es a través del denominado Quorum Sensing (QS). El QS en bacterias puede describirse como: un mecanismo de comunicación intra o interespecífico, en el que intervienen mediadores químicos (llamados autoinductores) capaces de inducir respuestas dependientes de la densidad de la población (Dos Santos Lima et al, 2019). El QS en bacterias constan de dos componentes principales: una proteína receptora y un autoinductor.…”
Section: La Rizósfera Y El Suelounclassified
“…La unión del autoinductor a su receptor activa el gen diana, que luego realiza la función correspondiente en bacterias (Yi, Dong, Grenier, Wang y Wang, 2021). Muchas bacterias Gram negativas utilizan autoinductores como las N-acil-homoserina lactonas (AHL) para controlar la expresión génica (Dos Santos Lima et al, 2019). El QS en estas bacterias suele ser un sistema de dos componentes integrado por una sintasa (LuxI), responsable de la producción de las moléculas autoinductoras, y un receptor sensor (LuxR), responsable de la detección de las moléculas en el ambiente (Barriuso y Martínez, 2018).…”
Section: La Rizósfera Y El Suelounclassified
“…With this array of benefits, significant effort has been given to understanding the microbial interactions that influence the association and colonization of A. brasilense and other diazotrophic bacteria with non-leguminous maize (Zea mays) crops (Dent and Cocking, 2017;Oliveira et al, 2018;Van Deynze et al, 2018). Prior studies have also shown that co-inoculation of A. brasilense with complementary organisms such as Bradyrhizobium (Wang et al, 2018;dos Santos Lima Fagotti et al, 2019) and cyanobacteria isolates (Hungria et al, 2010;Verma et al, 2011;Ferreira et al, 2013;Bashan et al, 2014) improves maize yield. This suggests that A. brasilense applied in a symbiotic, multi-species consortium may be key for its improvement as a biofertilizer.…”
Section: Introductionmentioning
confidence: 98%